PENGARUH PENGELOLAAN SUKU CADANG TERHADAP KELANCARAN OPERASIONAL PADA PT PELAYARAN SAMUDERA RIZQI : Bahasa Indonesia - Pahri Herdiansya; bahasa indonesia; Melia Handayani (Riset Sains dan Teknologi Kelautan, 2025)
This study aims to describe the condition of spare parts management and operational smoothness, as well as to analyze the influence of spare parts management on operational smoothness at PT Pelayaran Samudera Rizqi. The research employed a descriptive quantitative approach using a survey method. Data were collected through questionnaires distributed to 60 respondents who are active employees of the company. The descriptive analysis results show that the average score for spare parts management is 4.08 and for operational smoothness is 4.03, both of which fall into the "good" category. Simple regression analysis yielded a t-value of 8.369, which is greater than the t-table value of 1.671, with a significance level of 0.001. This indicates a significant influence of spare parts management on operational smoothness. The coefficient of determination (R Square) is 0.547, suggesting that 54.7% of the variation in operational smoothness is explained by spare parts management, while the remaining 45.3% is influenced by other factors outside the scope of this study. The resulting regression equation model is Y = 11.695 + 0.805X. These findings emphasize that effective spare parts management plays a crucial role in supporting the smooth operation of shipping company activities. Keywords: spare parts management, shipping, operational smoothness